The Effect of Risk Management Implementation on Financial Performance at Kalteng Development Bank Kuala Kapuas Branch - Haidir Ahsana; Fifi Swandari (Cita Konsultindo Research Center, 2024)
This study aims to analyze the effect of Non Performing Loans (NPL) (X1), Loan to Deposit Ratio (LDR) (X2), BOPO (X3), as exogenous variables on Return On Assets (ROA) (Y) as an endogenous variable accompanied by CKPN (Z) as an intervening variable at Bank Pembangunan Kalteng, Kuala Kapuas Branch. This study uses secondary data sourced from the financial statements of the company's bank for the period 2021-2023 obtained through the company's website. The method used in this study is a census using all samples in the population during that period. This study uses the path analysis method to determine the direct and indirect effects between exogenous variables on endogenous variables accompanied by intervening variables processed using the SmartPLS 3.0 program. The results of the study indicate that the NPL, LDR and CKPN variables have a negative effect on ROA, while the BOPO variable has a positive effect on ROA. The NPL variable has a negative effect on CKPN, while the LDR and BOPO variables do not affect CKPN. The results of the mediation effect test indicate that the intervening variable CKPN is able to provide an indirect effect on the relationship between NPL and ROA, while the effect of the LDR and BOPO variables on ROA cannot be mediated by CKPN.